1994
DOI: 10.1007/bf00007927
|View full text |Cite
|
Sign up to set email alerts
|

Seedling root response of some Kenyan bread wheat cultivars grown in acid nutrient culture solution containing aluminum

Abstract: The objective of this study was to determine whether a series of Kenyan bread wheat cultivars differed in tolerance to aluminum toxicity. Fourteen Kenyan wheat cultivars representing current and former widely grown cultivars of diverse pedigree origin, and two control cultivars, Maringa (Al-tolerant) and Siete Cerros (Al-susceptible), were tested in solution cultures with 0 (control), 148, 593, and 2370 t~M A1 at pH4.6. Highly significant (p ~<0.01) differences in seedling growth were observed among cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The highland areas of wheat production in Kenya: Molo, Mau Narok (Central Rift), Eldoret and Endebess (North Rift) have a pH of 4.3−5.5 [56]. All wheat cultivars grown in these areas have shown susceptibility to the pathogen but no direct screening has been done.…”
Section: Other Wheat Diseases In Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…The highland areas of wheat production in Kenya: Molo, Mau Narok (Central Rift), Eldoret and Endebess (North Rift) have a pH of 4.3−5.5 [56]. All wheat cultivars grown in these areas have shown susceptibility to the pathogen but no direct screening has been done.…”
Section: Other Wheat Diseases In Kenyamentioning
confidence: 99%
“…All wheat cultivars grown in these areas have shown susceptibility to the pathogen but no direct screening has been done. Aluminum toxicity in acid soils has been documented as the primary factor in the reduction of the crop yields [56]. Seed borne nature of the disease has been reported in wheat cultivars in Kenya [57,58], and studies on disease management revealed that the pathogen can be reduced by the use of seed treatment fungicides [59].…”
Section: Other Wheat Diseases In Kenyamentioning
confidence: 99%